CF‐related diabetes: Containing the metabolic miscreant of cystic fibrosis. (17th July 2017) - Moheet, Amir; Moran, Antoinette
Abstract: Cystic fibrosis‐related diabetes (CFRD) is associated with both an increase in morbidity and mortality in people with cystic fibrosis (CF). With increased screening and improved life expectancy of people with CF, the prevalence of CFRD is expected to rise further. The underlying pathophysiological mechanisms causing glucose intolerance and diabetes in patients with CF are not well understood but both functional and structural abnormalities in islet cells are likely to have key roles. Insulin therapy improves health outcomes in patients with CF. Future research is needed to better understand the mechanisms underlying the development of CFRD and to develop new screening and treatment strategies to minimize the detrimental impact of CFRD on health outcomes in people with CF.